Sites de redes sociais na educação: do entretenimento à formação para a cidadania - CALAÇA, Gabriella Luccianni Morais Souza (2011)
The number of Internet users has been increasing considerably in Brazil. According to surveys, social networks, such as Orkut, are among the most frequently accessed sites. However the digital divide still affects one third of the Brazilian population. As an argument to decrease this exclusion from the digital world, to prepare the students for the work environment and develop citizenship awareness, information and communication technologies have been implemented in schools run by the governments. The focus however, has been restricted to providing the physical facilities, in the form of laboratories. While social network sites are being used outside school hours and facilities by students and teachers to meet friends, communicate, update profiles and even to mobilize segments of the population, inside these institutions access to these social network sites is prohibited. The justification is that these tools do not serve educational purposes. The main objective of this survey, therefore, is to find out if the social networks available in the Internet can be used to further educational goals and to develop citizenship. To answer this question 23 tutors at the Núcleos de Tecnologia Educacional NTE (Centers for the use of Technology for Educational Purposes), responsible for offering courses in information technology to other tutors and teachers employed in State-run schools, were interviewed. The aim of the survey, therefore, is to determine the real situation in the public schools in Goiânia, regarding the use of social networks in the classroom.